Home vegetable gardening. Tape 09. Compost and mulch - applying organic matter to the soil. - Evans, John, Professor (Teacher); Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Extension Service, 1977)
Discusses the application of organic matter to soil. Manure spreading, composting, hot beds, decomposing organisms and accelerators, and mulching are all explained.